Pengembangan Modul Elektronik Interaktif Berbasis Exe-Learning dengan Pendekatan Saintifik pada Materi Gerak Melingkar Beraturan - Lintang Nurhayati; Rini Budiharti; Dwi Teguh Rahardjo (Universitas Sebelas Maret, 2023)
This study aims to describe the characteristics of Exe-Learning based electronic modules on physics material of Regular Circular Motion class X SMA and describe the assessment category of Exe-Learning based electronic modules on Regular Circular Motion material class X SMA by expert validators. The research model used in this research is Research and Development. The method used in this research is the development method with the ADDIE development model which is limited to three stages namely Analysis, design, and development. The data taken in the form of quantitative and qualitative data obtained from research subjects, namely expert validators, educators, and students. The data collection technique used a questionnaire technique. The data analysis used refers to the rating scale and interview by Sugiyono and the number line by Riduwan and Sunarto. The conclusion of this research is (1) the Exe-Learning-based electronic module on physics material for class X SMA regular circular motion has interactive characteristics in accordance with the scientific stages and consists of module cover, author biography, preface, table of contents, glossary, KI and KD, concept maps and competency maps, chapter 1 introduction, chapter 2 learning, evaluation, and closing, (2) based on expert assessments and the results of trials to students as research subjects, Exe-Learning-based electronic modules on physics material for class X SMA Regular Circular Motion based on material aspects, language aspects, and display aspects are categorized as at least good. After being tested to students, this module can be used in learning high school physics on the material of Regular Circular Motion.